(untitled) (Medical Forum Monthly, 2024)
Objective: To study the incidence of Bacteria resistance to antibiotics in hospitals. Study Design: Experimental study. Place and Duration of Study: This study was conducted at Shaheena Jamil Teaching Hospital Abbotabad & Islam Teaching Hospital Sialkot from 1st January 2012 to 30th April 2013. Materials and Methods: 100 cases of Bacteria resistance to antibiotics in hospital patients were selected by doing culture & sensivity test in labs of Shaheena Jamil hospital Abbottabad and Islam teaching hospital Sialkot. Results: Bacteria resistant to Penciline was the most highest, 147 cases (36.75%) & the lowest incidence of bacteria resistant to Levofloxin, 20 cases (05%) as shown in table No.1. The incidence of bacteria resistant to antibiotics with relation to age was maximum at 1-10 years, 15 cases (3.75%) & maximum in age group 21-30 years, 105 cases (25.75%) as shown in table No.2. The incidence of bacteria resistant to antibiotics in females were, 207 cases (51.75%) & in male, 193 cases (48.25%) as shown in table No.3. The incidence of bacteria resistant to antibiotics was the highest in office servants & factory workers, 54 cases ( 13.50%) & 53 cases (13.25%) respectively & the lowest in students, 20 cases (05%) as shown in table No.4. The incidence of bacteria resistant to antibiotics was highest in middle class of peoples, 189 cases (47.25%),159 cases (39.75%) in low socio-economic group of peoples & 52 cases in high gentry, 52 cases (13%) as shown in table No.5. The incidence of bacteria resistant to antibiotics was more in peoples living in rural area, 221 cases (55.25%) as compared to peoples living in urban area. 179 cases (44.75%) as shown in table No.6. Conclusion: The incidence of Bacteria resistance to antibiotics was rising day by day misuse of antibiotics, therefore the use of antibiotics should be only by a qualified doctor prescription.